Ethics and politics in ColombiaMartí, that mystery which can accompany us - Arenas-Amorocho, Héctor (Universidad Pedagógica y Tecnológica de Colombia, 2013)
On January 3, 1880, José Martí came to New York from his exile in Spain, after his imprisonment in Cuba. He came to live in what he called «the most free and great people of the earth» and declared himself happy to live in a country «where everyone seems to be his own master». He came with the open wound from the island still under peninsular aristocracy.